Form № 089/u-kv as the main tool of statistical accounting dermatovenereologist: basics of proper registration - M. V. Juchkov; M. A. Tarasova; D. B. Sonin (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
An integral part of the physician practices in modern conditions is the proper design and provision of appropriate scientific accounting and reporting of statistical information. One of the main tools of statistical accounting in dermatovenerology is the form № 089/u-kv. This account form of statistical observations in the practice of dermatologist, as well as other professionals who have the right to provide it, always causes some difficulties in the process of clearance and the order of granting. Accordingly the intention of this article is the explanation of certain provisions of guidelines for completing the form № 089/u-kv.